Clinical manifestations and laboratory findings of 496 children with brucellosis in Van, Turkey. Issue 4 (21st May 2015) - Parlak, Mehmet; Akbayram, Sinan; Doğan, Murat; Tuncer, Oğuz; Bayram, Yasemin; Ceylan, Nesrin; Özlük, Suat; Akbayram, Hatice Tuba; Öner, Abdurrahman
Abstract Background Brucellosis is the most common zoonotic disease worldwide and remains an important human disease especially in developing countries. The aim of the present study was to evaluate clinical manifestations and laboratory findings of childhood brucellosis in Van province of Eastern Turkey. To our knowledge, this is the largest series of childhood brucellosis reported in the literature. Methods In this retrospective study, 496 children with brucellosis were assessed for the clinical manifestations and laboratory findings from July 2009 through December 2013. The diagnosis of brucellosis was based on clinical findings and a standard tube agglutination test (titer ≥1:160). Data were analyzed using Minitab version 16. Results The study included 496 children (boys, 60.5%) with a mean age of 10.0 ± 3.95 years (range, 1–16 years). The most frequent clinical symptoms were arthralgia (46.2%), fever (32.1%), and abdominal pain (17.1%) and the most common clinical signs were peripheral arthritis (10.1%), splenomegaly (2.2%) and hepatomegaly (1.8%). The most contagious seasons were summer and autumn (63.3%). Elevated lactate dehydrogenase and C‐reactive protein and erythrocyte sedimentation rate were reported in 63.1%, 58.7%, and 55.2% of the patients, respectively. Anemia (20.4%), thrombocytopenia (15.5%), and leukopenia (12.1%) were the most common hematologic findings. Conclusions Brucellosis remains a serious public health problem in Turkey. The clinical and laboratory characteristics of childhood brucellosis have been described in order to assist clinicians in diagnosing and monitoring the disease.